Sosiologi Pendidikan Islam - M Syakur (Al-Riwayah : Jurnal Kependidikan, 2015)
Despite having different economic doctrines, capitalism, Marxism, and Islamic Economics share and maximize utilization of the nature in their doctrines. The three doctrines agree the importance of these objectives, as well as in the realization according to the lines of each doctrine. Economical Sociology studies many complex activities that involve production, distribution, exchange, and consumption of goods and services hardly found within communities, which focuses on economic activities, and the relationship among sociological variables involved in non-economic context. Concept of production in Islamic economics is always based on the philosophy of Islamic economics itself. Islamic economics philosophy provides spirit to the value of Islamic teaching and to production factors. These factors of production are: manpower, capital, natural resources, and skills/technology. The production concept in Islamic economics especially for capital factor is based on mudharabah and profit sharing. In the other side, conventional economics is based on interest using loans from conventional bank to finance production activities. Thus, production activities should be based on muamalah principles, such as tawhid, khilafah and ‘adl